Insecurity and Economic Stability in Nigeria Fourth Republic, 2013-2022 - Benedict Ighoshemu; Zephaniah Osuyi Edo; Helen Kpohraror (Journal of Research and Innovation, 2023)
Nigeria struggles for a stable nation with a lot of security challenges bedeviling her development. Although, it is not an uncommon situation to other African countries, Nigeria insecurity situation has become a monster since 2015. Insecurity is a feeling of not been safe and living in a state of fear. The study investigates the effects of the contemporary Nigeria security challenges on her economy, using historical method which involves the systematic collection and analysis of secondary data scooped from articles, textbooks, and internet materials. The paper adopted the systems theory of David Easton (1966) to enable us to understand the components and dynamics of a system in order to interpret the problem of insecurity and develop intervention strategies. The study reveals that there is a link between insecurity and economic instability in Nigeria. It recommends a pro-active and coordinated approach in combating insecurity problem with a view to increasing economic stability of the country.